Structural, phonon, mechanical, optical, and thermodynamic properties of stable β-La2S3 from first-principles calculations - 张显 桂文华 吴茜 曾庆丰 (Journal of rare earths, 2017)
The band structures,density of states,phonon,optical properties,and thermodynamic properties of β-La_2S_3 were calculated from first-principles using the plane-wave pseudopotential method.First,the structures were fully relaxed through the first-principles method.Then,the zone-center phonon-mode frequencies were evaluated within the framework of density functional perturbation theory.Properties related to the structure,phonons,optics,elastic constants,and thermodynamics of β-La_2S_3 were reported.The dielectric function,refractive index,absorption coefficient,extinction coefficient,infrared（IR） reflectance,energy,heat capacity,and Debye temperature spectra were also given β-La_2S_3 was a direct-gap semiconductor,and calculation indicated that its energy gap was 0.191 eV.From the phonon spectra,it could be concluded that the lattice dynamics were stable.A strong IR reflection occurred in a range of 0-1000 nm,arising from several strong IR-active modes,resulting in poor transmission properties.Relatively good transmission properties were observed in the range above 2000 nm,with low reflectivity and dissipation due to the absence of IR-active or weak modes.